5(u-2)-4=-2(-8u+6)-3u

Simple and best practice solution for 5(u-2)-4=-2(-8u+6)-3u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(u-2)-4=-2(-8u+6)-3u equation:



5(u-2)-4=-2(-8u+6)-3u
We move all terms to the left:
5(u-2)-4-(-2(-8u+6)-3u)=0
We multiply parentheses
5u-(-2(-8u+6)-3u)-10-4=0
We calculate terms in parentheses: -(-2(-8u+6)-3u), so:
-2(-8u+6)-3u
We add all the numbers together, and all the variables
-3u-2(-8u+6)
We multiply parentheses
-3u+16u-12
We add all the numbers together, and all the variables
13u-12
Back to the equation:
-(13u-12)
We add all the numbers together, and all the variables
5u-(13u-12)-14=0
We get rid of parentheses
5u-13u+12-14=0
We add all the numbers together, and all the variables
-8u-2=0
We move all terms containing u to the left, all other terms to the right
-8u=2
u=2/-8
u=-1/4

See similar equations:

| y=-30 | | -40+x=23-6x | | 14x+3=9x+7 | | (7x)=(10x-15) | | 7-3(7-2p)=p+21 | | 1.07^x=6,5 | | 1/5x=7–-4/5x | | p/4+10=4 | | 16x=2x+27.4 | | 14p–8=22+20p | | 643=4×164+n | | 30-5p=-3(p-8) | | -20•4x=-0.5x+22 | | 3x+7=2×(x+4)+1 | | 4-6(x-2)=3(x-1)+8 | | -3+3x=4x+8 | | -10–2b=-b | | 20x=20x+17 | | -5=x/13 | | 8k-2(5k-8)=-21 | | 37x+30=9x+42 | | x+4/4=-4 | | 20x=-20x | | 3n^2-5=-48 | | 6x+2/2x=x+23 | | 2x-23=-4x+43 | | 6x+8-3(-3x-1)=7(x-1) | | 1/(-5x-3)=14 | | -5t-2.2=2.9 | | 107+x=x+77 | | 100x^+49=0 | | n/2-2=-5 |

Equations solver categories